Saracatinib Fails to Reduce Alcohol-Seeking and Consumption in Mice and Human Participants - Thompson, Summer L.; Gianessi, Carol A.; O'Malley, Stephanie S.; Cavallo, Dana A.; Shi, Julia M.; Tetrault, Jeanette M.; DeMartini, Kelly S.; Gueorguieva, Ralitza; Pittman, Brian; Krystal, John H.; Taylor, Jane R.; Krishnan-Sarin, Suchitra (Frontiers in Psychiatry, 2021)
More effective treatments to reduce pathological alcohol drinking are needed. The glutamatergic system and the NMDA receptor (NMDAR), in particular, are implicated in behavioral and molecular consequences of chronic alcohol use, making the NMDAR a promising target for novel pharmacotherapeutics. Ethanol exposure upregulates Fyn, a protein tyrosine kinase that indirectly modulates NMDAR signaling by phosphorylating the NR2B subunit. The Src/Fyn kinase inhibitor saracatinib (AZD0530) reduces ethanol self-administration and enhances extinction of goal-directed ethanol-seeking in mice. However, less is known regarding how saracatinib affects habitual ethanol-seeking. Moreover, no prior studies have assessed the effects of Src/Fyn kinase inhibitors on alcohol-seeking or consumption in human participants. Here, we tested the effects of saracatinib on alcohol consumption and craving/seeking in two species, including the first trial of an Src/Fyn kinase inhibitor to reduce drinking in humans. Eighteen male C57BL/6NCrl mice underwent operant conditioning on a variable interval schedule to induce habitual responding for 10% ethanol/0.1% saccharin. Next, mice received 5 mg/kg saracatinib or vehicle 2h or 30-min prior to contingency degradation to measure habitual responding. In the human study, 50 non-treatment seeking human participants who drank heavily and met DSM-IV criteria for alcohol abuse or dependence were randomized to receive 125 mg/day saracatinib (n=33) or placebo (n=17). Alcohol Drinking Paradigms (ADP) were completed in a controlled research setting: before and after 7-8 days of treatment. Each ADP involved consumption of a priming drink of alcohol (0.03mg%) followed by ad libitum access (3h) to 12 additional drinks (0.015g%); the number of drinks consumed and craving (Alcohol Urge Questionnaire) were recorded. In mice, saracatinib did not affect habitual ethanol seeking or consumption at either time point. In human participants, no significant effects of saracatinib on alcohol craving or consumption were identified. These results in mice and humans suggest that Fyn kinase inhibition using saracatinib, at the doses tested here, may not reduce alcohol consumption or craving/seeking among those habitually consuming alcohol, in contrast to reports of positive effects of saracatinib in individuals that seek ethanol in a goal-directed manner. Nevertheless, future studies should confirm these negative findings using additional doses and schedules of saracatinib administration.